Optimalizatin The Role Of Gadgets As A Medium Learning Tahfidzul Qur'an - Muhammad Khoiruddin; Ahmad Faiz (Indonesia, 2021)
This research descreption are based on the rampant the phenomena of the use of gadgets in their business over the daily activity by all groups within the community without looking at the age limits of and the sexes, in practice these marketing almost all users of gadgets a small number of participants oblivious of dangers of the total value of negative a result of the use gadgets that is exaggerated. This research descreption how efforts to optimize the role of gadgets in daily life especially for education that was held in SMP Islam Pecangaan Jepara. This study attempts to get understanding whole about optimizing this role of the gadgets as a medium learning on the subjects of Tahfidz, empirical were based on the data to be implemented in the field show that 80 percent other students SMP Islam Pecangaan Jepara is using gadgets, methods used in the study analysis by approach deskreptif analytic outlined based on the findings in the field. From the results of research deskrepsi it can be concluded that the optimization of the role gadgets, as the media on the subjects Tahfidz striking result. it is an will have very significant in supporting the success of learning.